Investigating the Role of Digital Game Applications in Enhancing Mathematical Thinking Skills in Primary School Mathematics Students - Ali Ahmad Al-Barakat; Abdalla Falah El-Mneizel; Sami Sulieman Al-Qatawneh; Rommel Mahmoud AlAli; Yusra Zaki Aboud; Nahla Abbas Hilmi Ibrahim (Decision Making: Applications in Management and Engineering, 2025)
Digital gamification develops critical thinking skills through engaging students in problem-solving via interactive learnings and challenging tasks. Therefore, the study aimed to investigate the role of game applications in the mathematical thinking skills of Jordan primary school students. Data was collected from 162 mathematics primary school students through the purposive sampling technique. Both pre-test and post-test analyses were conducted for both of control and experimental groups. The results in the analysis of covariance (ANCOVA) showed a statistically significance difference in the use of digital game applications over the traditional methods. Furthermore, gender differences were also shown statistically difference but this impact was very limited with male students outperforming female students in the post-test. However, no significant interaction effects were found between the teaching methods and gender. This study with its significant findings contributes to the fields of educational technology and mathematics education by demonstrating the effectiveness of digital game applications in improving mathematical thinking skills. It highlights the potential of these applications to not only enhance computational skills but also to promote critical thinking and problem-solving in mathematics. Moreover, the research emphasized the importance of integrating digital tools into curricula to support various learning styles and needs. The findings also raise important questions regarding gender-based learning differences which is setting the stage for future research that explores learning strategies to address these disparities.